2020
DOI: 10.1007/s00415-020-09701-x
|View full text |Cite
|
Sign up to set email alerts
|

Single mean arterial blood pressure drops during stroke thrombectomy under general anaesthesia are associated with poor outcome

Abstract: Background We examined the influence of periprocedural blood pressure (BP), especially critical BP drops, on 3-month functional outcome in stroke patients undergoing mechanical thrombectomy (MT) under general anaesthesia (GA). Methods We screened all patients with anterior circulation large vessel occlusion receiving MT under GA at our centre from January 2011 to June 2016 and selected those who had continuous invasive periinterventional BP monitoring. Clinical and radiological data were prospectively collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
(33 reference statements)
2
7
0
2
Order By: Relevance
“…Consistent with previous studies, the multivariate analysis of our patient cohort identified age, baseline NIHSS, ASPECTS, and recanalization as predictive of functional outcomes after AIS 6,7,29–31. BP has been shown to be another modifiable factor influencing functional recovery after MT for AIS independent of anesthetic choice 29–34.…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with previous studies, the multivariate analysis of our patient cohort identified age, baseline NIHSS, ASPECTS, and recanalization as predictive of functional outcomes after AIS 6,7,29–31. BP has been shown to be another modifiable factor influencing functional recovery after MT for AIS independent of anesthetic choice 29–34.…”
Section: Discussionsupporting
confidence: 87%
“…The effect of procedural BP during EVT is mostly analyzed in conjunction with the type of anesthesia; therefore, the BP profile in such reports cannot be entirely distinguished from its influence (Table 2). 40,[43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] It is not uncommon during general anesthesia (GA) to have hypotensive episodes due to anesthesia drugs, intravascular hypovolemia, high intrathoracic pressures, and impaired sympathetic tone. 62 GA is usually correlated with lower BP levels and unfavorable outcomes compared to local anesthesia or conscious sedation.…”
Section: Levels and Variabilities Of Blood Pressure In Peri-endovascular Treatment And Stroke Outcomesmentioning
confidence: 99%
“…Even single mean arterial blood pressure drop during mechanical thrombectomy under general anesthesia could result in poor neurologic outcome. In retrospective cohort study of 115 subjects that underwent to mechanical thrombectomy under general anesthesia, it was found that subjects that suffered from drops in the mean arterial blood pressure below 60 mmHg faced a worse outcome [ 13 ]. If mechanical thrombectomy will be performed under general anesthesia, the anesthesia team has to be aware that even short episodes of the hypotension during the general anesthesia induction can result in impairment of the collateral circulation.…”
Section: Management Of the Blood Pressure In Acute Ischemic Stroke Before And During Endovascular Recanalizationmentioning
confidence: 99%